DESIGNING DIGITAL LEARNING FRAMEWORKS FOR PAKISTANI SCHOOLS: A PRACTICAL APPROACH - Shazadi Hina Sain; Zohaib Hassan Sain; Aulia Luqman Aziz; Nurulannisa Abdullah (jfpublisher, 2025)
The integration of digital technologies into education has emerged as a transformative strategy for addressing challenges in Pakistani private schools. This research investigates the effectiveness of digital tools in designing inclusive and impactful learning plans, employing theoretical frameworks such as TPACK, SAMR, and the 5E instructional model. The study examines how these tools enhance curriculum delivery and student engagement, with a specific focus on platforms like Padlet, Nearpod, and FigJam. This qualitative research utilised a sample of 20 Grade 2 students and 31 teachers from private schools, chosen for their established yet diverse technological infrastructure. The mixed-methods approach included surveys, semi-structured interviews, and classroom observations to evaluate the application and impact of digital technologies. The study also explored how these tools align with educational objectives and cater to varying learner needs. Key findings reveal that digital technologies significantly enhance collaboration, critical thinking, and differentiated learning experiences, particularly benefiting visual and auditory learners. However, challenges such as inconsistent internet access, limited resources, and varying teacher competencies were identified. The research proposes actionable strategies to address these barriers, including professional development for educators, improved infrastructure, and tailored digital solutions. This study highlights the critical role of digital tools in fostering scalable and inclusive learning environments. It underscores the need for sustained investment in technology integration and teacher training to ensure equitable access and maximise the potential of digital education in resource-constrained contexts. Future implications suggest adopting innovative models and policies to bridge digital divide and enhance learning outcomes across diverse educational settings.